Analysis of Sarawak Bario rice diversity using microsatellite markers - Wong, Sie Chuong; Yiu, Pang Hung; Bong, S. T. W.; Lee, Huei Hong; Neoh, Phene Pei Nee; Amarthalingam, Rajan (Science Publications, 2009)
Problem statement: There are numerous claims on varieties of Bario rice cultivars in Sarawak. Many of them might be synonyms or homonyms. This preliminary study was to differentiate Bario Rice cultivars using microsatellite molecular markers. Approach: Microsatellite marker panels distributed on all 12 chromosomes on rice genome were employed to study 8 Bario rice cultivars in Sarawak. Results: Current study indicated that the microsatellite panel were able to differentiate the 8 Bario rice cultivars. A total of 31 alleles were generated at 12 polymorphic microsatellite loci among the cultivars using the selected polymorphic SSR primer pairs with an average of 2.6 alleles per locus. Average PIC value obtained was 0.5204. An UPGMA dendrogram based on SSR polymorphism indicated high variation among the rice varieties with the coefficient ranging from 0.16 and 0.92. Genetic diversity determination using cluster analysis showed differentiation of rice cultivars into 2 major groups and several sub-groups. Conclusion: The SSR markers were useful for differentiating the genotypes and assessment of genetic relationships due to its reproducibility and to multiallelic, codominant and informative properties.